Pelatihan Penggunaan Aplikasi E-Koperasi Untuk Meningkatkan Pelayanan Perkoperasian Pada Koperasi Simpan Pinjam Di Kota Jambi - Lazuardi Yudha pradana; Ahmad Husaein (LPPM Universitas Dinamika Bangsa, 2023)
Cooperative digitalization is one of the strategies in an effort to increase the acceleration of cooperative growth. during the pandemic, cooperatives had problems in running their business. By digitizing cooperatives, it is hoped that cooperatives can easily run their activities and businesses. The E-Cooperative application is an application designed to realize transparency in the management of cooperatives related to members' savings and loans. E-Cooperatives are developed through Web-Based Applications and Android. However, along with the implementation of the application so far there are still many cooperative managers and administrators who do not understand the technicalities of using and managing E-cooperative applications so that the benefits of the application cannot be felt optimally. Therefore, the Jambi City cooperatives & UKM service deems it necessary to have training on using the E-cooperative application which is attended by all managers of savings and loan cooperatives under the auspices of the cooperative service which technically takes part in 30 participants.